A Proof of Concept of XR Application in the Construction of Logistics Warehouses - Jácome, Jarbas; Alvez, Luís E. M.; Brazileiro, Ricardo (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
This proof of concept introduced Pernambuco’s industries to the new possibilities offered by XR technologies. Through the HoloLens 2, SVR 2024 attendees will be able to visualize an example of a logistics warehouse rendered in 3D within the real environment using augmented reality. The logistics company that experienced this PoC expressed interest in further exploring XR applications.